Analisis Penggunaan Media Video Animasi terhadap Motivasi Belajar PAI Siswa di Kelas 3 SDN 18 Karan Aur - Laili, Iga Hijratul; Alfurqan, Alfurqan (Lembaga Yasin AlSys, 2024)
This research is motivated by the use of appropriate learning media by teachers so that students have motivation in participating in learning, this media is animated video media. This research aims to determine the use of animated video media in the 3rd grade Islamic Religious Education subject at SDN 18 Karan Aur and to determine the supporting and inhibiting factors in the use of animated video media on student learning motivation in the 3rd grade Islamic Religious Education subject at SDN 18 Karan Aur . This research uses descriptive qualitative methods, the object of this research is grade 3 students at SDN 18 Karan Aur and the subject of this research is students' learning motivation. Then data is obtained from observation, interviews and documentation to see existing phenomena. The results of this research show that the use of animated video media in Islamic Religious Education subjects in class 3 of SDN 18 Karan Aur is very good and appropriate to use because it really helps students in the learning process. Students have high enthusiasm and enjoyment for Islamic Religious Education lessons so that they have strong determination and will in carrying out learning activities, students have the desire to succeed, there is encouragement and need in learning, there are hopes and aspirations, there is appreciation for learning, there are interesting activities in learning, the creation of a conducive learning environment. So it is proven that the use of animated video media in learning can increase students' learning motivation.